High prevalence and diversity of Bartonella in small mammals from the biodiverse Western Ghats. - B R Ansil; Ian H Mendenhall; Uma Ramakrishnan (Public Library of Science (PLoS), 2021)
Bartonella species are recognized globally as emerging zoonotic pathogens. Small mammals such as rodents and shrews are implicated as major natural reservoirs for these microbial agents. Nevertheless, in several tropical countries, like India, the diversity of Bartonella in small mammals remain unexplored and limited information exists on the natural transmission cycles (reservoirs and vectors) of these bacteria. Using a multi-locus sequencing approach, we investigated the prevalence, haplotype diversity, and phylogenetic affinities of Bartonella in small mammals and their associated mites in a mixed-use landscape in the biodiverse Western Ghats in southern India. We sampled 141 individual small mammals belonging to eight species. Bartonella was detected in five of the eight species, including three previously unknown hosts. We observed high interspecies variability of Bartonella prevalence in the host community. However, the overall prevalence (52.5%) and haplotype diversity (0.9) was high for the individuals tested. Of the seven lineages of Bartonella identified in our samples, five lineages were phylogenetically related to putative zoonotic species-B. tribocorum, B. queenslandensis, and B. elizabethae. Haplotypes identified from mites were identical to those identified from their host species. This indicates that these Bartonella species may be zoonotic, but further work is necessary to confirm whether these are pathogenic and pose a threat to humans. Taken together, these results emphasize the presence of hitherto unexplored diversity of Bartonella in wild and synanthropic small mammals in mixed-use landscapes. The study also highlights the necessity to assess the risk of spillover to humans and other incidental hosts.